2012
DOI: 10.1182/blood.v120.21.491.491
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of ADAMTS13 in Platelets As a Novel Therapeutic Approach for Arterial Thrombosis

Abstract: 491 Megakaryocytes and platelets have been shown to produce ADAMTS13 and its only known substrate, von Willebrand factor (VWF). However, the role of platelet expression of ADMTS13 in modulation of thrombus formation is not known. Previous studies have shown that platelet-targeted delivery of clotting factor VIII corrects bleeding phenotype in hemophilia A mice despite of inhibitors. These results suggest that platelet-delivery of ADAMTS13 may also be efficacious for anti-arterial thrombosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The biological function of platelet‐derived ADAMTS‐13 remains unknown. Preliminary study from our laboratory, presented in the 54th Annual Meeting of the American Society of Hematology, demonstrated that transgenically overexpressed ADAMTS‐13 in the platelets of Adamts13 −/− mice is releasable upon activation by thrombin and collagen, as well as during the thrombus formation after injury with 10% ferric chloride . The secreted human ADAMTS‐13 was able to dramatically inhibit thrombus growth in mesenteric arterioles after oxidative injury and protects Adamts13 −/− mice from VWF‐ and shiga toxin‐induced ‘TTP‐like’ syndrome .…”
Section: Biosynthesis and Secretion Of Adamts‐13mentioning
confidence: 97%
“…The biological function of platelet‐derived ADAMTS‐13 remains unknown. Preliminary study from our laboratory, presented in the 54th Annual Meeting of the American Society of Hematology, demonstrated that transgenically overexpressed ADAMTS‐13 in the platelets of Adamts13 −/− mice is releasable upon activation by thrombin and collagen, as well as during the thrombus formation after injury with 10% ferric chloride . The secreted human ADAMTS‐13 was able to dramatically inhibit thrombus growth in mesenteric arterioles after oxidative injury and protects Adamts13 −/− mice from VWF‐ and shiga toxin‐induced ‘TTP‐like’ syndrome .…”
Section: Biosynthesis and Secretion Of Adamts‐13mentioning
confidence: 97%